Role of Neuroimaging as a Biomarker for Neurodegenerative Diseases - Shimizu, Soichiro; Hirose, Daisuke; Hatanaka, Hirokuni; Takenoshita, Naoto; Kaneko, Yoshitsugu; Ogawa, Yusuke; Sakurai, Hirofumi; Hanyu, Haruo (Frontiers in Neurology, 2018)
Neurodegenerative diseases are increasingly being recognized to occur by common cellular and molecular mechanisms, including protein aggregation and inclusion body formation. Each type of neurodegenerative disease is characterized by the specific protein that aggregates. There is now an increased understanding of the pathways involved in protein aggregation, and some clues have recently emerged as to the molecular mechanisms resulting in cellular toxicity. These are leading to approaches toward rational therapeutics. Neurodegenerative diseases are fundamentally diagnosed pathologically. Therefore, autopsy is essential for a definitive diagnosis of a neurodegenerative disease. However, recently, the development of various molecular brain imaging techniques have enabled pathological changes in the brain to be inferred even without autopsy. Some molecular imaging techniques are described as biomarker in diagnostic criteria of neurodegenerative disease. Magnetic resonance imaging (MRI), Single photon emission computed tomography (SPECT:), positron emission tomography (PET) and amyloid imaging are described in the diagnostic guidelines for Alzheimer’s disease in the National Institute on Aging-Alzheimer’s Association. MRI, dopamine transporter (DAT) imaging, and 123I-metaiodobenzyl-guanidine (MIBG) myocardial scintigraphy listed in the guidelines for consensus clinical diagnostic criteria for dementia with Lewy bodies are described as potential biomarkers. The Movement Disorder Society Progressive supranuclear palsy Study Group defined MRI, SPECT/PET, DAT imaging, and Tau imaging as biomarkers. Other diagnostic criteria for neurodegenerative disease described neuroimaging findings as only characteristic finding, not as biomarker. In this review, we describe the role of neuroimaging as a potential biomarker for neurodegenerative diseases.